Pragmatic Properties of Text Units and Prescriptions - Abduhamidovna, Nurmanova Dilfuza (European Journal of Life Safety and Stability (2660-9630), 2021)
In particular, the general knowledge of the speaker in the pragicate speech, their common knowledge of the object of speech, their language of the context obviously, there is no doubt that the aspects of nicts.